A review of the hyperiidean amphipod superfamily Lycaeopsoidea Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea) - Zeidler, Wolfgang (Zootaxa, 2004)
A taxonomic review of the superfamily Lycaeopsoidea is presented. The superfamily currently consists of one family represented by one genus with two species. A detailed morphological examination of many specimens, of both species, supports the superfamily status, based on the extreme sexual dimorphism and characters of the antennae and mouthparts unique to the Hyperiidea. In males the peduncle and first flagellar articles of the first antennae form a triangular structure with the remainder of the flagellum inserted subterminally. Contrary to recent literature, second antennae are present in both sexes, although much reduced in size, consisting of five articles. The mandible is reduced to an elongate bifid pincer, without a palp in females but in males the palp usually consists of one elongate article, resulting from the fusion of the three articles normally found in the Amphipoda. New information and a key is provided to separate the two closely related species.